Hybrid governance model in formulating public policy on forest conservation based on local wisdom ontology - Nahak, Hildigardis Maria Imakulata; Liliweri, Aloysius; Djaha, Ajis Salim Adang; Neolaka, Melkisedek N.B.C (International Journal of Communication and Society, 2025)
The purpose of this study is to find a Hybrid Governance model in the formulation of public policies for forest conservation based on local wisdom ontology. The method used is qualitative with a critical emic ethnography approach. The theory used is the theory of public administration. There are several data collection techniques used to obtain the necessary information, namely observation, in-depth interviews and document studies. In this study, data analysis was carried out qualitatively. The data analysis process includes several activities, namely: data collection, data condensation, data presentation (data display) and data conclusions (conclusions: drawing/verifying). The results of the study show that traditional ecological knowledge (TEK) in the Tetun community is manifested through the practice of crop rotation, seasonal prohibitions, sacred zone arrangements such as lulik, rai-mutin, and rai-klaran, as well as collective rites that strengthen the spiritual relationship between humans and nature. The customary sanction mechanism and social oversight through customary leaders such as na'i, tua adat, and kukun demonstrate that customary institutions function as normative and operational tools in maintaining ecological balance. However, in the context of public policy at the village level, indigenous community participation remains procedural. Musrenbang (Regional Development Planning Forum) and village planning documents (RPJMDes and RKPDes) have not substantively accommodated the results of customary deliberations. Village governments tend to use technocratic and formal legal approaches that are not always aligned with the value systems of indigenous communities. This indicates an imbalance between the formal epistemology of the state and the local epistemology of indigenous communities. The most prominent contribution of this research is the formulation of a Hybrid Governance Model Based on Tetun Customs, which integrates customary institutions into the formal village government system.